PROFIL ECOLITERACY MAHASISWA PENDIDIKAN BIOLOGI DALAM MATA KULIAH EKOLOGI HEWAN - Murti, Warda; Rohman, Facthur; Saptasari, Murni; Ibrohim, Ibrohim (Jurnal Binomial, 2025)
This study aims to determine the ecoliteracy skills of students in animal ecology courses. This research was conducted on 174 biology education students at six universities in South Sulawesi. This study used descriptive quantitative research. Data on ecoliteracy skills were collected using a multiple choice test technique of 25 items that had been validated by two material experts. The results of this study indicate that based on Goleman's five indicators of ecoliteracy, there are three indicators that are still classified as low, namely aspects of practice, visibility and evaluation of facts while the other two indicators are classified as excellent, namely aspects of empathy and real solutions.